Synthesis and anticonvulsant activity of some alkanamide derivatives - Tarikogullari, Ayse H.; Kilic Fatma, Sultan; Erol, Kevser; Pabuccuoglu, Varol (Arzneimittelforschung, 2010)
A group of JV-phenylacetamide, N-phenylpropanamide and N-benzylamide derivatives bearing 5-membered heterocyclic rings such as pyrazole, 1, 2, 4-triazole and imidazole rings at ω position were synthesized and their anticonvulsant activity was evaluated in the maximal electroshock test. The results indicated that the 1, 2, 4-triazole ring leads to superior activity than the pyrazole ring and inserting a CH2 group into the anilide structure leading to N-benzyl derivatives did not change the anticonvulsant activity, but caused a noticeable decrease in duration of action. The most active compound was 2-(lH-l, 2, 4-triazole-l-yl)-N-(2, 6-dimethylphenyl) acetamide.
Keywords: Alkanamide; Anilide; Anticonvulsant drugs; Imidazole; Pyrazole; Triazole